Competition, monopoly, and corporate governance : essays in honour of Keith Cowling - Cowling, Keith; Waterson, Michael (Cheltenham, UK : Northhampton, MA : Edward Elgar Pub., 2003)
Written in honour of Professor Keith Cowling, Professor of Economics at University of Warwick, these essays offer an overview of the current state of play in related areas including: market structure, corporate power and governance, technical change and social welfare.
Includes bibliographical references and index.
oif 21/07/16
Loans
Keywords: International economic relations; Globalization; Globalization; Technological innovations; Competition, International